Unusual Bronchial Foreign Bodies with Localized Bronchiectasis in Five Children. (28th December 2019) - Wu, Xi-Ling; Wu, Lei; Chen, Zhi-Min
Abstract : Obstructive foreign bodies are uncommon causes of bronchiectasis in children, the causal relationship between foreign body aspiration and bronchiectasis remains unclear. We conducted a review of children who were diagnosed with bronchiectasis due to foreign body retention in a university hospital between 2014 and 2019. Five patents were studied (four boys, one girl; age range: 15 months to 13 years old). Computed tomography showed localized cylindrical bronchiectasis in all five patients. After removal of the foreign body by bronchoscopy, the prognoses were good. Patients with localized cylindrical bronchiectasis should be examined to exclude foreign body. As long as foreign body aspiration is diagnosed early and appropriately removed, the possibility of a lobectomy or even mortality is greatly reduced.